Gender Justice and Liberation in the Interpretation of the Qur'an: A New Reading of Q.S. 4: 34 - Ahmad Hamdani; Nur Fitriana; Baharuddin (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2025)
This article explores the reinterpretation of Qur'an 4:34 through a comparative analysis of two contemporary Islamic hermeneutical models: Fazlur Rahman's ethical-historical “double movement” and Farid Esack's liberationist approach. This article aims to respond to the continued misuse of this verse to justify patriarchal authority and domestic violence, particularly in Muslim-majority societies. Using qualitative textual analysis, this study examines the socio-historical context of the verse and its ethical implications, as understood by Rahman, along with Esack's emphasis on social justice, victim-centered exegesis, and advocacy for the mustad‘afīn (the oppressed). This research highlights how both scholars reject literalist readings and advocate for justice-centered interpretations that align with the Qur’anic values of compassion (rahmah) and justice (‘adl). Rahman's methodology provides a historical reconstruction that invalidates wife beating in a modern context, while Esack's liberation theology redefines nushūz and centers Qur'anic exegesis on the dignity of marginalized individuals. The synthesis of their models has been shown to support reform in Islamic education, gender-inclusive curricula, and anti-violence legal policies. These findings underscore that integrating ethical and liberation paradigms can produce a dynamic and socially responsive hermeneutics of the Qur'an. This approach contributes to contemporary Islamic scholarship by offering a theological foundation for gender justice and promoting interpretations that are contextually grounded and ethically empowering.